Answer:
1) 4·(n + 9) = 4·n + 4·9; Distributive Property
2) (6·7)·m = 6·(7·n); Associative Property of Multiplication
3) b · 1 = b; Multiplicative Identity Property
4) a + (-a) = 0; Additive Inverse Property
Explanation:
1) The given equation and the properties that justifies the equation are;
4·(n + 9) = 4·n + 4·9
The above equation can be written as follows;
4 × (n + 9) = 4 × n + 4 × 9
Therefore, the common factor, 4 is distributed across the to the two terms inside the parenthesis, which gives the property as distributive property
2) (6·7)·m = 6·(7·n)
The above equation gives the association of the product of the first two terms on the left multiplied by the third term being equal to the product of the first term and the association of the product of the last two terms on the right of the term on the right hand side of the equation
Therefore, we have associative property of multiplication
3) b · 1 = b
The value of the product of any variable and 1 is the value of the variable
Therefore, we have the multiplicative identity property
4) a + (-a) = 0
The sum of a variable (or number) and the negative (or opposite) of the variable (or number) is 0
Therefore, we have the additive inverse property